PENGELOLAAN SERVICE QUALITY : DAMPAKNYA TERHADAP CUSTOMER SATISFACTION - Ekowati, Titin (Fokus Ekonomi, 2006)
Focus on customer ( customer oriented) through excellent service will be effective to retain customer. Informations, critics and suggests from customer should be responsed quickly. So customer not switching to competitor’s products. Strategy to retain the customer can build with the best service quality manage and this condition will be impact to the customer than create customer satisfaction. At the moment customer satisfaction represent norm obliged to given by every organization. Besides, reseach proves that satisfaction unable to guarantee the happening of customer loyalty. Manager should be create customer delight, not only customer satisfaction but also customer delight. Because the empirical research show that the relationship between satisfaction and loyalty have low corelation or not significant relationship. Only the customer delight can create the loyalty of the customer to the company.Keywords : Service Quality, Customer Satisfaction, Customer Delight, Loyalty